Autonomous wearable sensor nodes with flexible energy harvesting - Toh, Wang Yun (2021)
Distributed wearable wireless sensors are widely employed in wireless body sensor network for various physiological monitoring purposes like health or performance related monitoring applications. The real challenges in employing these wearable wireless sensors on human subjects include: 1) bulky and rigid system design thus, it is difficult to conform to human body contour and 2) limited operational lifespan of batteries with finite energy supply. In this paper, an autonomous body-worn wireless sensor node with flexible energy harvesting (FEH) mechanism, able to conform to body contour, is proposed for biometric monitoring. To be totally sustainable and compact, the FEH mechanism is equipped with an ultralow power management circuit (PMC) specially designed on a flexible PCB. The flexible PMC is able to transfer near maximum electrical power from the input solar energy source to store in the supercapacitor for powering the wireless sensor node. The power consumption of the flexible PMC is only 32.86 μW. Experimental results show that under indoor condition, typical average lighting intensity of 320 lux, the wearable sensor node is able to continuously monitor the temperature of the wearer, read, and transmit back to the base node in a wireless manner, without the need of any battery. In addition, the designed FEH sensor node flexed onto the wearer body contour at an angle of 30° generates 56 μW of electrical power, sufficient to sustain its operation for >15h.